John Tyler papers - Tyler, John, 1790-1862.; Tyler, Julia Gardiner, 1820-1889.; Tyler, Lyon Gardiner, 1853-1935.
Correspondence and other papers, including correspondence of Tyler's widow, Julia Gardiner Tyler, an autograph collection assembled by their son, Lyon Gardiner Tyler, and family papers reflecting social life and customs in Virginia. Correspondents include George Bancroft, James Barbour, Margaret Gardiner Beeckman, Richard T. Brown, James Buchanan, John S. Cunningham, Henry Curtis, John B. Floyd, Alexander Gardiner, Juliana McLachlan Gardiner, Thomas W. Gilmer, Hugh Blair Grigsby, Mary Tyler Jones, John Leeds Kerr, James Lyons, James Monroe, Cincinnatus Newton, John Page, Littleton W. Tazewell, St. George Tucker, Septimus Tustin, Robert Tyler, and Henry A. Wise.
Series 1-3 available on microfilm
Microfilm produced from originals in the Manuscript Division.
President of the United States; vice-president under William Henry Harrison; U.S. representative and senator from Virginia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index published by the Library of Congress in 1961 available in the Library of Congress Manuscript Reading Room. Cataloged in record 60060078.
Keywords: Bancroft, George, -- 1800-1891 -- Correspondence; Barbour, James, -- 1775-1842 -- Correspondence; Beeckman, Margaret Gardiner, -- 1822-1857 -- Correspondence; Brown, Richard T. -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Cunningham, John S., -- active 1851-1856 -- Correspondence; Curtis, Henry, -- 1792-1862 -- Correspondence; Floyd, John B. -- 1806-1863 -- Correspondence; Gardiner, Alexander, -- 1818-1851 -- Correspondence; Gardiner, Juliana McLachlan, -- 1799-1864 -- Correspondence; Gilmer, Thomas Walker, -- 1802-1844 -- Correspondence; Grigsby, Hugh Blair, -- 1806-1881 -- Correspondence; Harrison, William Henry, -- 1773-1841.; Jones, Mary Tyler, -- 1815-1848 -- Correspondence; Kerr, John Leeds, -- 1780-1844 -- Correspondence; Lyons, James, -- 1801-1882 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Newton, Cincinnatus -- Correspondence; Page, John, -- 1787-1865 -- Correspondence; Tazewell, Littleton Waller, -- 1774-1860 -- Correspondence; Tucker, St. George, -- 1752-1827 -- Correspondence; Tustin, Septimus -- Correspondence; Tyler, Robert, -- 1816-1877 -- Correspondence; Tyler family; Wise, Henry A. -- 1806-1876 -- Correspondence; Autographs -- Collections; United States -- Politics and government -- 1841-1845.; Virginia -- Politics and government -- 1775-1865.; Virginia -- Social life and customs; Governors -- Virginia; Presidents -- United States; Representatives, U.S. Congress -- Virginia; Senators, U.S. Congress -- Virginia; Vice-Presidents -- United States